2009
DOI: 10.1029/2007jg000641
|View full text |Cite
|
Sign up to set email alerts
|

Atmosphere and hydrological controls of the evapotranspiration over a floodplain forest in the Bananal Island region, Amazonia

Abstract: [1] This article discusses seasonal and interannual variations of the evapotranspiration (ET) rates in Bananal Island floodplain, Brazil. Measurements included ET and sensible heat flux using the eddy covariance method, atmospheric forcings (net radiation, Rn, vapor pressure deficit, VPD, wind speed and air temperature), soil moisture profiles, groundwater level and flood height, taken from November 2003 to December 2006. For the hydrological years (October-September) of 2003/2004, 2004/2005 and 2005/2006, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
0
11

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(94 citation statements)
references
References 25 publications
3
80
0
11
Order By: Relevance
“…2 shows that equatorial forests exhibit a seasonal cycle of E peaking with net radiation during the dry season, transitional southern forests show either a flat seasonal cycle (due to less seasonality in available light) or a slight dry season depression (some degree of water limitation), and Cerrado demonstrates a strong dry season depression (both due to reductions in light and water). These results corroborate those of previous work which showed a general trend of increasing water limitation from north to south (Hasler and Avissar, 2007;Juarez et al, 2007;Borma et al, 2009;da Rocha et al, 2002da Rocha et al, , 2009Fisher et al, 2009). While BAN and RJA differed slightly in their respective seasonalities of E (BAN has a more pronounced dry season depression compared to RJA), overall the individual site E seasonalities corresponded to the mean E seasonality of the grouped sites (see Appendix D of the supplement for individual site seasonalities).…”
Section: Site and Model Representation In Analysessupporting
confidence: 81%
See 2 more Smart Citations
“…2 shows that equatorial forests exhibit a seasonal cycle of E peaking with net radiation during the dry season, transitional southern forests show either a flat seasonal cycle (due to less seasonality in available light) or a slight dry season depression (some degree of water limitation), and Cerrado demonstrates a strong dry season depression (both due to reductions in light and water). These results corroborate those of previous work which showed a general trend of increasing water limitation from north to south (Hasler and Avissar, 2007;Juarez et al, 2007;Borma et al, 2009;da Rocha et al, 2002da Rocha et al, , 2009Fisher et al, 2009). While BAN and RJA differed slightly in their respective seasonalities of E (BAN has a more pronounced dry season depression compared to RJA), overall the individual site E seasonalities corresponded to the mean E seasonality of the grouped sites (see Appendix D of the supplement for individual site seasonalities).…”
Section: Site and Model Representation In Analysessupporting
confidence: 81%
“…While both models with these modifications simulate the overall seasonality of E well, the observations indicated slight reductions in E during the dry season in June through September, which were best captured by SiB3. Surprisingly, the water budget analysis for the BAN site (Borma et al, 2009) revealed that observed seasonal patterns of soil moisture storage and groundwater flux were not consistent with either of the deep soil/deep roots or groundwater formulations (Fig. 4f,h and j).…”
Section: Supply-side Mechanisms Of Ementioning
confidence: 99%
See 1 more Smart Citation
“…It is considered the largest fluvial island in the world (Borma et al 2009;Dias et al 2011;Devi 2012). The island is a floodplain temporarily flooded during the rainy season by precipitation of local waters, being classified as a seasonal wetland (Valente 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The dry season is from May to September (mean relative humidity of 40%), while the wet season is from October to April (mean relative humidity of 90%) (Borma et al, 2009). Plinth and Concretionary soils are the dominant soil types of the region, where can also be found Hydromorphic soils, Ox soils and Quartz sands (SEPLAN, 2008).…”
Section: Study Areamentioning
confidence: 99%